TINGKAT KEPUASAN KONSUMEN TERHADAP TOKO INATON FLOWER DI KELURAHAN MOLINOW KECAMATAN KOTAMOBAGU BARAT - Sri Wahyuni Laruke; Rine ., Kaunang; Oktavianus ., Porajouw (Sam Ratulangi University, 2021)
The objective of this research is to determine the level of consumer satisfaction with the product, price, place and service of the Inaton Flower Shop. This research was carried out from February to April 2021. The data used in this study are primary data and secondary data. Primary data were obtained through direct interviews with 30 respondents using a questionnaire measured using a Likert scale. Secondary data obtained through books, journals, and literature related to the topic of this research. The research result howed that the level of consumer satisfaction at the Inaton Flower Shop from the product, price, place, and service variables was 82.40%, generally classified as satisfied. The level of consumer satisfaction at the Inaton Flower Shop for the product variable is 83.11% classified as satisfied, the price variable is 82.33% classified as satisfied, and the place and variable is 84.44% satisfied. The service variable of 80.33% is classified as satisfied.